Study of B s 0 $$ B_{s}^0 $$ → J/ψπ+π − K+K − decays - The LHCb collaboration; R. Aaij; C. Abellán Beteta; T. Ackernley; B. Adeva; M. Adinolfi; H. Afsharnia; C. A. Aidala; S. Aiola; Z. Ajaltouni; S. Akar; J. Albrecht; et al. (Journal of High Energy Physics, 2021)
Abstract The decays B s 0 $$ {\mathrm{B}}_{\mathrm{s}}^0 $$ → J/ψπ+π − K+K − are studied using a data set corresponding to an integrated luminosity of 9 fb −1, collected with the LHCb detector in proton-proton collisions at centre-of-mass energies of 7, 8 and 13 TeV. The decays B s 0 $$ {\mathrm{B}}_{\mathrm{s}}^0 $$ → J / ψK ∗ 0 K ¯ ∗ 0 $$ \mathrm{J}/{\uppsi \mathrm{K}}^{\ast 0}{\overline{\mathrm{K}}}^{\ast 0} $$ and B s 0 $$ {\mathrm{B}}_{\mathrm{s}}^0 $$ → χc1(3872)K+K − , where the K+K − pair does not originate from a ϕ meson, are observed for the first time. Precise measurements of the ratios of branching fractions between intermediate χc1(3872)ϕ, J / ψK ∗ 0 K ¯ ∗ 0 $$ \mathrm{J}/{\uppsi \mathrm{K}}^{\ast 0}{\overline{\mathrm{K}}}^{\ast 0} $$ , ψ(2S)ϕ and χc1(3872)K+K − states are reported. A structure, denoted as X(4740), is observed in the J/ψϕ mass spectrum and, assuming a Breit-Wigner parameterisation, its mass and width are determined to be m X 4740 = 4741 ± 6 ± 6 MeV / c 2 , Γ X 4740 = 53 ± 15 ± 11 MeV , $$ {\displaystyle \begin{array}{c}{m}_{\mathrm{X}(4740)}=4741\pm 6\pm 6\kern0.5em \mathrm{MeV}/{c}^2,\\ {}{\Gamma}_{\mathrm{X}(4740)}=53\pm 15\pm 11\kern0.5em \mathrm{MeV},\end{array}} $$ where the first uncertainty is statistical and the second is systematic. In addition, the most precise single measurement of the mass of the B s 0 $$ {\mathrm{B}}_{\mathrm{s}}^0 $$ meson is performed and gives a value of m B s 0 = 5366.98 ± 0.07 ± 0.13 MeV / c 2 . $$ {m}_{{\mathrm{B}}_{\mathrm{s}}^0}=5366.98\pm 0.07\pm 0.13\kern0.5em \mathrm{MeV}/{c}^2. $$